Dataset for A process-oriented approach to equitable resilience: insights from droughts in Lake Naivasha Catchment Area, Kenya - Sayan, Caner; Liambila, Robai Namulekhwa; Wairimu, Edith Warigia; Wesonga, John; Hess, Tim M. (Cranfield University, 2026)
During the multiple field visits in May 2022, data collection was done using three principal approaches: small group discussions (SGDs), key informant interviews (KIIs), and field observations. The data collection was done in all the Water Resources User Associations (WRUA); the upstream, midstream, and downstream areas to capture all study areas‘ perceptions and views. Small groups consisted of a minimum of 2 and a maximum of 5 members. The SGDs and KIIs took a maximum of 40 minutes and were moderated by two people. There were seven SGDs, and five KIIs carried out in the study area. That number was reached as information saturation was attained. Open-ended questions were administered and also on the drivers, pressures, states and impacts of climate change. The sample was the representatives of all WRUAs existing in the catchment area, so that twelve WRUAs provided qualitative data for the project. Follow-up interviews were conducted with three out of twelve WRUAs in June 2022 to clarify certain points raised in the first round of data collection (May 2022) by the Kenyan team and Dr Sayan. Dr Sayan also noted his field observations during the visit. The first round of interviews were audio recorded, translated into English (when interviews were conducted in Swahili) and transcribed by the research team. Interviewees were anonymised using pseudonyms numbered 1–12 in the data files.
Keywords: Equitable resilience; environmental justice; droughts; smallholder farmers; Kenya